TRADISI MANTAB DALAM PENGEMBANGAN MASYARAKAT DI KECAMATAN GEDANGAN KABUPATEN SIDOARJO - Mazidah, Nur (The Sociology of Islam, 2012)
The research about â€œThe Study of Mantab Tradition for Community Development in Kecamatan Gedangan Kabupaten Sidoarjoâ€ is based on the idea that : 1) Mantab is one of social institution that serve the religious-social function, 2) Among perception of Gedanganâ€™s societies, Mantab tradition need to be developed and it has spectacular members, about 7000 people, 3) Mantab tradition has socio-cultural mechanism growth from local content. Its position very often become strategic tools for community development information. This research is focused on the following matters. 1) Social function of Mantab tradition as religious institution, 2) the perception of the community toward Mantab tradition and, 3) the real contributions of Mantab tradition in the process of community development. Theoretical concepts underlying this research are paradigm of structural-functional theory. In addition, it is aimed at discovering whether there is any relation between social function of institution as written in theory matches the fact found in the real life. The writer applies qualitative research using phenomenological approach. The technique used in this research is in-depth interview and observation. Purposive sampling used to get the whole information needed. Kata Kunci: tradisi Mantab, pengembangan masyarakat.